2016
DOI: 10.1590/1806-9282.62.09.837
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes after chemotherapy for trophoblastic neoplasia

Abstract: SUMMARY Introduction The successful development of chemotherapy enabled a fertilitysparing treatment for patients with trophoblastic neoplasia. After disease remission, the outcome of a subsequent pregnancy becomes a great concern for these women. Objective To analyze existing studies in the literature that describe the reproductive outcomes of patients with trophoblastic neoplasia treated with chemotherapy. Method Systematic review was performed searching for articles on Medline/ Pubmed, Lilacs and Cochran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
7
0
4
Order By: Relevance
“…A systematic review of 18 articles by Garcia et al in 2016 showed no evidence of decreased fertility after chemotherapy for gestational trophoblastic neoplasia, but a higher miscarriage rate was found in women who conceived within 6 months after chemotherapy compared with women who waited longer. 69 Also, older reports warn against pregnancy within a year after the end of multi-chemotherapy for gestational trophoblastic neoplasia because of a higher risk of recurrence of gestational trophoblastic disease (9.1%) and fetal wastage (27.3%). 70 Fertility and Reproductive Outcomes After Surgery in Highrisk Gestational Trophoblastic Neoplasia Surgery can be an important part of the treatment of high-risk gestational trophoblastic neoplasia.…”
Section: Reviewmentioning
confidence: 99%
“…A systematic review of 18 articles by Garcia et al in 2016 showed no evidence of decreased fertility after chemotherapy for gestational trophoblastic neoplasia, but a higher miscarriage rate was found in women who conceived within 6 months after chemotherapy compared with women who waited longer. 69 Also, older reports warn against pregnancy within a year after the end of multi-chemotherapy for gestational trophoblastic neoplasia because of a higher risk of recurrence of gestational trophoblastic disease (9.1%) and fetal wastage (27.3%). 70 Fertility and Reproductive Outcomes After Surgery in Highrisk Gestational Trophoblastic Neoplasia Surgery can be an important part of the treatment of high-risk gestational trophoblastic neoplasia.…”
Section: Reviewmentioning
confidence: 99%
“…MRI can provide a valuable tool for diagnosing ectopic hydatidiform moles through features like, intratumoral hypervascularity, molar tissue-like tiny cystic lesions and dense enhancement as cited in a previous study [9].Outcomes post laparoscopic salpingectomy for ectopic molar pregnancy are good, although the risk quantification for persistent disease after surgical removal is difficult due to scarcity of reported cases, In the previously described choriocarcinoma and invasive mole, chemotherapy was the treatment of choice [10]. About 5% and 15% of patients who are diagnosed with partial mole and complete mole, respectively, will acquire persistent gestational trophoblastic disease [7]. Proper differentiation between molar ectopic and non molar ectopic is hence mandatory.…”
Section: Discussionmentioning
confidence: 88%
“…Ectopic molar pregnancy was reported in the U.K at a rate of 1.5 in a 1000,000 [6]. Clinical symptoms, ultrasound imaging, quantitative BHCG level are salient aspects that aid the diagnosis of molar pregnancy [7]. It is noteworthy that BHCG levels in tubal molar pregnancy mimics that of an ectopic pregnancy, unlike the high values found in an intrauterine molar pregnancy [8].…”
Section: Discussionmentioning
confidence: 99%
“…The number of studies in the literature regarding this theme is small. The studies highlight that there is no change in fertility [18]. Under close monitoring, patients may conceive six months after achieving complete response [19].…”
Section: Discussionmentioning
confidence: 98%